2020
DOI: 10.18662/rrem/12.1sup2/253
|View full text |Cite
|
Sign up to set email alerts
|

Video Conferencing Integration: Challenges and Opportunities at Universities

Abstract: As teachers who experience challenges with delivering classes online and finding relevant ways to teach students, we suggest our practical recommendations on video conferencing tools integration at universities. This synchronous online tool is an efficient method of class delivery that provides practicing four key language skills, maintaining communication and facilitating digital competence development. The study involved 34 teachers from two universities to share the experience, expectations, and perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Among the benefits of videoconferencing are enhancing communication and collaboration skills [22], the authenticity of interaction and educational materials [23]; possibility of case-presentations which encouraged active students' participation in discussions [24]; development of peer-assessment skills [25]; self-initiated learning in asynchronous mode [26], interactivity, ease of use, engaging learning environment [27].…”
Section: Online Learning Tools In Medical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the benefits of videoconferencing are enhancing communication and collaboration skills [22], the authenticity of interaction and educational materials [23]; possibility of case-presentations which encouraged active students' participation in discussions [24]; development of peer-assessment skills [25]; self-initiated learning in asynchronous mode [26], interactivity, ease of use, engaging learning environment [27].…”
Section: Online Learning Tools In Medical Educationmentioning
confidence: 99%
“…We should take into account that high-quality and unlimited video-conferencing systems are quite expensive. Also, among the problems are class management, assessment techniques, lack of teachers' confidence and self-efficacy, time-consuming preparation of all materials, students' loss of attention and concentration [27]. According to Rafi et al [7], the duration of synchronous video lesson should not exceed 45 minutes, this is the optimal time for effective material perception, distribution of attention and ensuring the balance between the psychological and physical health of the student.…”
Section: Online Learning Tools In Medical Educationmentioning
confidence: 99%
“…ODL is not a new concept. “However, only now has it become a unique resource to satisfy the educational needs” ( Mukan and Lavrysh, 2020 , p. 109). It was not included under the frame of formal education until the spread of COVID-19 ( Harizan et al, 2016 ) because of manifold problems that need fixing ( Gabelaia, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the introduction of quarantine restrictions and the transition of educational institutions to distance learning, educators around the world have been trying to answer these questions and evaluate the effectiveness of distance learning, particularly for higher education (Can Aksu, 2020;Naciri et al, 2020;Pokhrel & Chhetri, 2021;Brammer & Clark, 2020;Eric M. Anderman & Sungjun Won, 2019). In Ukraine, the problems of online learning during quarantine have also been studied quite intensively (Lavrinenko, 2020;Soter, 2020;Mizyuk, 2019;Mukan & Lavrysh, 2020;Lukianenko & Vadaska, 2020;Lytovchenko & Voronina, 2020). Malovany (2020) found that the main problems faced by the participants of educational interactions in distance learning include: lack of quality Internet communication, incomplete provision of participants of the educational process with the necessary technical equipment, lack of previous experience and knowledge of the methodology of distance learning.…”
Section: Introductionmentioning
confidence: 99%